Cos2x = sin³x + cos³x
cos²x - sin²x = (sinx + cosx)(sin²x - sinxcosx + cos²x)
(cosx - sinx)(cosx + sinx) - (sinx + cosx) (1 - sinxcosx) = 0
(sinx + cosx)(cosx - sinx - 1 + sinxcosx) = 0
(sinx + cosx)(cosx - 1 + sinx(cosx - 1) = 0
(sinx + cosx)(cosx - 1)(1 + sinx) = 0
Произведение равно нули, если один из множителей равен нули. Составим совокупность:
sinx + cosx = 0 | :cosx
cosx - 1 = 0
1 + sinx = 0
tgx + 1 = 0
cosx = 1
sinx = -1
tgx = -1
cosx = 1
sinx = -1
x = - pi/4 + pi*n
x = 2pi*n
x = - pi/2 + 2pi*n
n принадлежит Z
Ответ: - pi/4 + pi*n; 2pi*n; - pi/2 + 2pi*n; n принадлежит Z.